Konstruksi Makna Postingan Instagram @Najwa Shihab Dalam Membangun Citra Diri ( Analisis Semiotika Ferdinand De Saussure ) - Salsa Ratu Maisya; K.Y.S. Putri (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
The use of social media such as Instagram is not only for communication and sharing moments such as photos and videos but Instagram can also be used as a medium in building one's self-image in any aspect, in achieving positive and negative images, on other Instagram users. One of them is Najwa Shihab, who in fact is a public figure who often uses Instagram to share valuable moments when creating his own image. The purpose of this research is to find out the construction of Najwa Shihab's self-image on Instagram social media. As for the paradigm itself, it uses a constructivist paradigm with descriptive research type and a qualitative approach method with Ferdinand de Saussure's semiotic theory. In this study, the object of his research is in the form of photos and descriptions on the @najwashihab Instagram account. The results of this study are to make components of how to form a self-image, where there are verbal and nonverbal messages seen from the sentences or captions he wrote with a characteristic and the style of photography and fashion worn by Najawa Shihab. Therefore, this study concludes that Najwa Shihab has several characteristics in building his self-image which is simple, educational, smart, humble, modern, fashionable and inspiring.